2020
DOI: 10.48550/arxiv.2003.07143
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Unconventional phases in a Haldane model of dice lattice

Bashab Dey,
Priyadarshini Kapri,
Ojasvi Pal
et al.

Abstract: We propose a Haldane-like model of dice lattice analogous to graphene and explore its topological properties within the tight-binding formalism. The topological phase boundary of the system is identical to that of Haldane model of graphene but the phase diagram is richer than the latter due to existence of a distorted flat band. The system supports phases which have a 'gapped-out' valence (conduction) band and an indirect overlap between the conduction (valence) band and the distorted flat band. The overlap of… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…The presence of an unusual band structure in α-T 3 model can lead to unique and unexpected features, including electronic, [58][59][60] collective, [61][62][63] magnetic, [64] optical properties, [65][66][67][68][69] and even a phase transition [70]. These behaviors are very different from those of graphene.…”
Section: Of 18mentioning
confidence: 99%
“…The presence of an unusual band structure in α-T 3 model can lead to unique and unexpected features, including electronic, [58][59][60] collective, [61][62][63] magnetic, [64] optical properties, [65][66][67][68][69] and even a phase transition [70]. These behaviors are very different from those of graphene.…”
Section: Of 18mentioning
confidence: 99%
“…27 It was also demonstrated that the off-resonant field could substantially modify transport properties 17,41,42 , excitonic behavior 43 and topological signatures of a two-dimensional lattice. 29,[44][45][46] A molybdenum disulfide MoS 2 is one of monolayer transition-metal dichalcogenides with a distorted tetragonal structure. [47][48][49] In general, the monolayer semiconducting MoS 2 structure may assume a trigonal prismatic coordination of the metal atoms (2H with hexagonal symmetry), as well as octahedral coordination (1T with tetragonal symmetry) or 1T with a distorted and the most exotic 50,51 which is exactly the subject of our study.…”
Section: Introductionmentioning
confidence: 99%
“…32 Meanwhile, it was demonstrated that the off-resonant field could substantially modify transport properties 21,46,47 , RKKY interaction 16,48 , excitonic dynamics, 49 and topological signatures of a two-dimensional lattice. 34,[50][51][52] Topological effects on various two-dimensional lattices in the presence of elliptically-polarized light were studied in Ref. [53].…”
Section: Introductionmentioning
confidence: 99%